Case Report: Splenic Mucormycosis; A Post-Covid Sequelae - Guragain, Ankita; Shrestha, Sanjeet Krishna; Ghimire, Subodh; Dhakal, Sunil Kumar Sharma (Journal of Advances in Internal Medicine, 2022)
Introduction: Mucormycosis is an invasive disease associated with high mortality ranging from 25-62%. There is an increase in the incidence of mucormycosis in post COVID-19 infection patients. Case presentation: A 55 year old male presented to the emergency department with complain of pain abdomen and with a past medical history of renal transplantation and recent COVID-19 infection. On CT abdomen evaluation he was found to have hypodense spleen suggestive of splenic abscess. Investigations and Treatment: Splenectomy was done, which on microbiological examination revealed mucormycosis. The patient was treated with amphotericin B for 3 weeks followed by posaconazole for another 2 weeks. Discussion: Mucormycosis, although a rare infection, has been classically linked to organ transplantation which can also be considered as a possible reason for immunosuppression in this case. Transplant physicians must be aware that patients with COVID-19 are at risk of developing unusual opportunistic infections.